What Britain did to Nigeria: a short history of conquest and rule - Siollun, Max (London: Hurst & Company, 2024)
"What Britain Did to Nigeria" examines British colonial rule in Nigeria, emphasizing the negative consequences of conquest and rule, including violence, the exploitation of ethnic and religious divisions, and the lasting impact on Nigerian culture and politics. The book challenges narratives that portray colonial rule as benevolent, highlighting the ways in which Britain's actions created or exacerbated many of Nigeria's current problems.
Includes bibliography and index
nmn 11/06/2025
Loans
Keywords: Colonization - Britain; Colonization - Nigeria; Colonial influence - Nigeria; Great Britain - Colonies; Nigeria